Fenomena Perilaku LGBT di Kalangan Muslim dan Kristen: Studi Kasus Media Sosial - Safitri, Dewi; Harahap, Elly Warnisyah; Paralihan, Hotmatua (ANWARUL, 2023)
The Phenomenon of LGBT Behavior Among Muslims and Christians: A Case Study of Social Media. While the type of research used by the author is a library research. As for the data analysis using descriptive qualitative methods, content analysis comparative methods, and hermeneutic methods. Problems on social media related to LGBT come from pornographic sites where users can easily participate, share and create content in the virtual world which is immediately widespread, apart from that there are facts proving this deviation, also because this issue is a classic issue that then it is developing again at the present time, especially in the community and has a very negative impact because it can damage the morale of the nation's children and is very contrary to religious norms, values and Pancasila. This research approach takes the historical approach method. The results of this study indicate that the phenomenon of LGBT (Lesbian, Gay, Bisexual and Transgender) is a group that has a different sexual orientation than heterosexuals. In Indonesia, it began to be advertised openly in people's lives. Many people claim that they are LGBT. For Muslims and Christians in Indonesia about the Sodom people at the time of Prophet Lut who were punished by God for same-sex sexual behavior that deviated and left religious teachings. One of the developments of LGBT is the spread of social media where users can communicate, share and create content by spreading photos or videos. The issue of sexual deviance has become the object of debate where people still think that LGBT behavior is an act that is not appropriate. And some people think that everyone has the right to freedom of belief, express thoughts and attitudes according to their conscience.This finding is in accordance with Akhmad Said Asrori The Executive Board of Nadhlatul Ulama (PBNU) emphasized that he rejects the practice or actions of Lesbian, Gay, Bisexual, and Transgender (LGBT) because it greatly deviates from the teachings of Islam. All Muslims are obliged to guide LGBT actors to the right path. Research, these findings disagree with the world leader Barrack Obama who legalized same-sex marriage and indicated that he supports LGBT people. Same-sex couples who wish to marry, can register their marriage at the US civil registry office.